Muslim Ummah : Vision and Hope - Ibrahim, Anwar (Intellectual Discourse, 2013)
It is almost a decade since this university was established as an instrument to fulfil the highest hopes and aspirations of the ummah. These dawned upon us amidst a global environment that promised a significant role for the ummah in world affairs. It was an opportunity to move from a position of marginality to centre stage. A new consciousness began to take root amongst the youth. There was a new sense of confidence and a reassertion of our identity. This was the coming of the 15th century of Islam...